2020
DOI: 10.1002/pc.25768
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the mechanical and morphological behavior of Prosopis juliflora bark fibers/E‐glass/carbon fabrics reinforced hybrid polymeric composites for structural applications

Abstract: The present world scenario demands for the utilization of natural fiber-reinforced polymeric composites as opposed to synthetic fiber-reinforced composites mainly due to their environmental friendly behavior, availability in abundance, cost-effectiveness, and lightweight and moderately high-strength properties. Along with the above said advantages, the ease of manufacturing of natural fibers has made the researchers around the globe to exploit several locally available natural fibers to understand their feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…To further characterise the developed biocomposites, additional mechanical tests, such as compression, interlaminar, and in-plane shear tests, should be conducted. In particular, when analysing the bending stiffness results, a significant difference between the bio-epoxy and standard epoxy resins can be observed, a phenomenon also reported by Madhu et al [ 17 ]. This difference results from variations in the fibre–matrix adhesion, as natural fibres generally tend to cause far more problems (when untreated) than glass or carbon fibres.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…To further characterise the developed biocomposites, additional mechanical tests, such as compression, interlaminar, and in-plane shear tests, should be conducted. In particular, when analysing the bending stiffness results, a significant difference between the bio-epoxy and standard epoxy resins can be observed, a phenomenon also reported by Madhu et al [ 17 ]. This difference results from variations in the fibre–matrix adhesion, as natural fibres generally tend to cause far more problems (when untreated) than glass or carbon fibres.…”
Section: Discussionsupporting
confidence: 64%
“…Plates were fabricated (460 mm × 420 mm) with a thickness of at least 2 mm. From each test specimen, five were cut out of the plate, which is the minimum number of samples to analyse to obtain statistically viable data, according to all applicable testing standards [ 11 , 12 , 16 , 17 ]. For further investigation of the 90 green composites, considering the sheer number of specimens to be cut and the importance of their dimensional equality, all specimens were cut using a computer numerically controlled abrasive water jet cutting machine.…”
Section: Methodsmentioning
confidence: 99%
“…Dry sliding wear performance of the manufactured composites was analyzed on a pin-on-disc machine, (Make: DUCOM, India) as per ASTM G99 standard. [36] The experiments were conducted for different normal load (10,15,20,25, and 30 N) and sliding speed (1.5, 2.5, 3.5, 4.5, and 5.5 m/s) in EN-32 steel disc with 50 mm track diameter for fixed sliding distance of 1000 m. The 20 mm × 5 mm × 5 mm size sample was held within the holder perpendicular to the steel disc. Before and after the sliding wear experiments, sample weight was measured by using a digital electronic balance and reported as volumetric wear by using following equation:…”
Section: Testing Methodologymentioning
confidence: 99%
“…The hybridization of kenaf/pineapple was reported to increase the mechanical and water absorption resistance of polypropylene hybrid composites by N. L. Feng et al. [19] P. Madhu et al [20] and T. G. Y. Gowda et al [21] concluded that the evaluated mechanical properties were significantly increased for hybridization of Prosopis juliflora-glass-carbon and flax-basalt-carbon fiber reinforced polymer composites. Caryota urens natural fiber and glass fiber reinforced nanoclay/SiC toughened epoxy nanocomposite were reported to exhibit excellent mechanical and wear properties by P. Raju et al.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Moreover, several researchers have established the correlations between the morphologies and mechanical properties of PU/EP IPNs or fiber reinforced composite at submicron or nanoscale. [13,22,23] However, the correlation on the nanomechanical and macromechanical properties of IPNs is still lacking.…”
Section: Introductionmentioning
confidence: 99%